A Case of Acquired Smooth Muscle Hamartoma on the Sole - Lee, Deborah (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
A smooth muscle hamartoma is a benign proliferation of smooth muscle bundles within the dermis. It arises from smooth muscle cells that are located in arrector pili muscles, dartos muscles, vascular smooth muscles, muscularis mammillae and the areolae. Acquired smooth muscle hamartoma (ASMH) is rare, with only 10 such cases having been reported in the English medical literature to date. Most of these cases of ASMH were shown to have originated from arrector pili and dartos muscles. Only one case was reported to have originated from vascular smooth muscle cells. A 21 year-old woman presented with a tender pigmented nodule, with numbness, on the sole of her foot, and this lesion had developed over the previous 18 months. The lesion showed no hyperpigmentation or hypertrichosis, and the biopsies demonstrated increased smooth muscle bundles in the dermis, and especially around the blood vessels. Moreover, the specimens stained positive with Masson trichrome stain and α-smooth-muscle actin antibodies, thus supporting our diagnosis of ASMH of the foot sole. Herein, we report on a rare case of ASMH on the foot sole, and this lesion originated from vascular smooth muscle cells. This type of case has not been previously described in the English medical literature.